Analisis Sistem Pembelajaran Daring Berbasis Gamification Collaboration untuk Mendukung Merdeka Belajar Menggunakan Octalysis Framework - Maukar, Anastasia Lidya; Vitianingsih, Anik Vega; Marisa, Fitri; Pramudita, Atanasia; Putri, Jessica Ananda; Pramisela, Intan Yosa (Universitas Merdeka Malang, 2022)
The COVID-19 pandemic has had a major impact on many things. Education, which is one of the important aspects in supporting human life, also felt the impact of the pandemic. Based on Circular Letter Number 4 of 2020 concerning the Implementation of Education Policies during the emergency period of the spread of COVID-19, the government has a policy that face-to-face education is not allowed to be carried out. Therefore, the world of education began to implement distance learning or e-Learning. Â In addition to how to teach and learn, there are other things that need to be considered for the success of the process. Another thing is student learning motivation. Changes in the teaching and learning process also have an impact on student learning motivation. In this study, a questionnaire has been distributed to find out the core drive of student learning motivation. Based on a questionnaire that has been filled out by 167 respondents, the core drive that influences students' learning motivation is at a high level. This indicates that the level of student learning motivation during the COVID-19 pandemic is still high.